Penang's Hajj Heritage: An Oral History of the Sea Transportation Era - Mahani Musa,; Aiza Maslan,; Hajar Abdul Rahim, (Kajian Malaysia, 2018)
For almost 200 years, from 1786 until 1977, Penang (also known as Pulau Pinang) was the embarkation point for hajj pilgrims from Malaya and other countries in the region, notably Siam (Thailand) and the Dutch East Indies (Indonesia). Its vibrant port enabled Penang to become a major centre for ocean going ships and transportation of hajj pilgrims. This long history only came to an end in 1977 when air transport took over the role of ships in transporting pilgrims to the holy land. Although stories of transportation and management of hajj pilgrims who travelled by sea to Mecca have appeared in official records, other aspects of this important era of Penang's hajj heritage remain unknown. The experiences, stories and memories of the pilgrims (men, women and children), hajj agents, health inspector, port police officer, local inhabitants, and others who were involved directly and indirectly in the hajj enterprise in Penang, have never been documented or made known to the public. Hence, the current hajj heritage project which sets out to bridge the lacunae in our knowledge of this important era of Penang's hajj heritage.